2010
DOI: 10.1186/1748-717x-5-39
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent radiochemotherapy in advanced hypopharyngeal cancer

Abstract: BackgroundConcurrent platinum-based radiochemotherapy has been recommended as a standard of care in patients with locally advanced squamous cell head and neck carcinomas. Unfortunately, there is a lack of level one evidence on best treatment approach for advanced hypopharyngeal cancer. This report aims to summarize the results of our study on concurrent radiochemotherapy in patients with advanced hypopharyngeal cancer.MethodsA retrospective analysis of 41 patients with stage III-IV hypopharyngeal cancer was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
1
9
2
Order By: Relevance
“…The oncologic outcomes reported in the present study were comparable to those published in other studies on locally advanced hypopharyngeal cancer [12,13,15]. Five-year OS rates ranging from 25 to 50% are usually published depending on the clinical characteristics of the patients and treatment modalities.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The oncologic outcomes reported in the present study were comparable to those published in other studies on locally advanced hypopharyngeal cancer [12,13,15]. Five-year OS rates ranging from 25 to 50% are usually published depending on the clinical characteristics of the patients and treatment modalities.…”
Section: Discussionsupporting
confidence: 88%
“…Unsurprisingly, patients treated by induction CT had higher OS, SS, and LRC rates (Table II) RT ± CT or primary TPL. Beside induction CT, primary concurrent RT + CT is another modality of larynx preservation in patients with locally advanced larynx or hypopharynx cancer [12,13]. To date, there is not a high scientific rationale supporting the superiority of TPF induction CT followed by RT ± CT or of primary concurrent RT + CT in this setting [3].…”
Section: Discussionmentioning
confidence: 98%
“…A retrospective analysis showed that the 2-year disease-free survival (DFS) and 2-year overall survival (OS) rates were only 29.3 and 32.8%, respectively, in patients with Stage III/IV hypopharyngeal cancer treated with CRT. The locoregional relapse-free survival rate at 2 years was 51.3% and distant metastasis-free survival rate at 2 years was 64.7% (11). A Phase II trial evaluating efficacy after treatment with induction chemotherapy followed by concomitant chemoradiotherapy in 59 patients with hypopharynx cancer or base of tongue cancer reported 3-year OS of 64% and PFS of 57% in all patients (4).…”
Section: Introductionmentioning
confidence: 99%
“…13 In developing countries including India hypopharyngeal cancers are relatively more common constituting 20 to 35% of all the head and neck cancers.…”
Section: Discussionmentioning
confidence: 99%